Best Answer

Take the two equations, and line them up with common terms in the same positions:

x - y = 6

x - 2y = 7

In this case, the operation is quite simple because x has no coefficient in either equation. You can simply subtract each term in the latter equation from it's corresponding term in the prior one:

x - y = 6

x - 2y = 7

___________

0 + y = - 1

So we know that y is equal to negative one, and you can solve for x by simply substituting that -1 into either equation:

x - (-1) = 6

x + 1 = 6

x = 5

So x is equal to five, and y is equal to negative one.

Q: How do i solve x-y equals 6 and x-2y equals 7 by elimination?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

If that's x2y and xy2, the GCF is xy.

(b - x)(ab - xy)

x+xy=8 xy=-x+8 y=-1+8/x

If you're solving for x, then x = 3/y.

4xy + x3y + yx2 + yx + 3yx = x3y + x2y + 8xy = (xy)(x2y + x + 8)

Related questions

The GCF is xy

xy

xy

4

If that's x2y and xy2, the GCF is xy.

(b - x)(ab - xy)

x+xy=8 xy=-x+8 y=-1+8/x

If you're solving for x, then x = 3/y.

4xy + x3y + yx2 + yx + 3yx = x3y + x2y + 8xy = (xy)(x2y + x + 8)

The GCF of 27 x^2 y^3 and 46 x^2 y is xy^2. 27 and 46 are coprime.

x2y + axy + abx + a2b Factor by grouping. xy(x + a) + ab(x + a) (xy + ab)(x + a)

Not sure that there is any name or description. For example, x2y, xy0.5, xy have the same variables but there is no name that encompasses all three.